Spiritualitas dan Akuntabilitas Manajerial dalam Filantropi Islam di Laz Sahabat Yatim Cab Makassar - Hariatih Hariatih; Alimuddin Alimuddin; Syarifuddin Syarifuddin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to explore how Islamic spirituality shapes managerial accountability within Islamic philanthropic organizations, with a focus on Sahabat Yatim Foundation, Makassar Branch. Using a qualitative interpretive approach, the research investigates the meaning of spirituality in the management of zakat, infak, and sadaqah funds through in-depth interviews, participant observation, and document analysis. The findings reveal that the four prophetic values siddiq (honesty), amanah (responsibility), tabligh (transparency), and fathanah (wisdom)serve as moral foundations that shape managerial consciousness and ethical behavior among organizational actors. These values operate not only as individual moral guides but also as embedded cultural principles that influence financial reporting, monitoring systems, organizational communication, and strategic decision-making. The integration of spirituality with digital transparency practices, particularly the implementation of an e-reporting system, strengthens public trust and enhances the institution’s moral and social legitimacy. The study concludes that accountability in Islamic philanthropy is not merely an administrative obligation but a manifestation of spiritual awareness and religious commitment to safeguarding public trust and managing communal funds with integrity. This research contributes to the theoretical development of spirituality-based accountability and offers practical implications for improving governance practices in Islamic philanthropic institutions in the digital era.